Germany: Myth and Apologia in Christa Wolf’s Novel Medea. Voices - Yixu Lü (PORTAL: Journal of Multidisciplinary International Studies, 2004)
In 1995, Christa Wolf, the most eminent author of the former German Democratic Republic, published the novel Medea. Voices. It takes up themes which have been worked and re-worked in European literature since Euripides’ tragedy, and which go back into pre-literary myth. Medea has many guises: she can be seen as the monstrous mother; as the victim of Jason’s fickle nature; or as the perpetual ‘stranger’, the woman who has given up all her origins, only to be disowned.

Christa Wolf’s novel concentrates on the impossibility of dialogue—not merely between different cultures, but also between the sexes within one culture. ‘Estrangement’ has come to define the human condition. In this—by no means novel—generalization of cultural antagonism to explain what makes human society violent, there lie many unanswered questions.

The hypothesis I offer is that such fictions lead to inaccurate generalizations if we take them as more than just elaborations of tragic myth. My paper will seek to narrow this focus once more—in a critical sense—by posing the question: to what extent does this specific adaptation of the myth by Christa Wolf reflect problems within the society of reunified Germany post-1989?